Contextualizing oppositional cultures: A multilevel network analysis of status orders in schools - Hanno Kruse; Clemens Kroneberg (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Different lines of research have argued that specific groups, such as boys or ethnic minorities, are more prone to develop an anti-school culture than others, leading to group differences in the social acceptance of high performers. Taking an ecological view, we ask to what extent the school context promotes or prevents the emergence of group-specific oppositional cultures. Theoretically, we argue that group-based oppositional cultures become more likely in schools with low socio-economic resources and in schools where socio-economic differences align with demographic attributes. We test our hypotheses based on data from a large-scale, four-wave network panel survey among more than 3000 students in Germany. Applying stochastic actor-oriented models for the coevolution of networks and behavior, we find that group-based oppositional cultures in which students like high performers less are very rare. However, in line with theoretical expectations, boys tend to evaluate high-performing peers less positively than girls do in schools that are less resourceful. Moreover, ethnic minority boys tend to evaluate high performers less positively than majority boys do in schools where the former tend to come from socio-economically less resourceful families.
Keywords: I24; Z13; 330; gender; ethnicity; school performance; social networks; stochastic actor-oriented models